A critical review on biomass gasification, co-gasification, and their environmental assessments - Somayeh Farzad; Mohsen Ali Mandegari; Johann F. Görgens (Biofuel Research Journal, 2016)
Gasification is an efficient process to obtain valuable products from biomass with several potential applications, which has received increasing attention over the last decades. Further development of gasification technology requires innovative and economical gasification methods with high efficiencies. Various conventional mechanisms of biomass gasification as well as new technologies are discussed in this paper. Furthermore, co-gasification of biomass and coal as an efficient method to protect the environment by reduction of greenhouse gas (GHG) emissions has been comparatively discussed. In fact, the increasing attention to renewable resources is driven by the climate change due to GHG emissions caused by the widespread utilization of conventional fossil fuels, while biomass gasification is considered as a potentially sustainable and environmentally-friendly technology. Nevertheless, social and environmental aspects should also be taken into account when designing such facilities, to guarantee the sustainable use of biomass. This paper also reviews the life cycle assessment (LCA) studies conducted on biomass gasification, considering different technologies and various feedstocks.